Combined adenocarcinoma–atypical carcinoid of the lung. Targeted Next-Generation Sequencing (NGS) suggests a monoclonal origin of the two components. Issue 3 (March 2018) - La Rosa, Stefano; Simbolo, Michele; Franzi, Francesca; Uccella, Silvia; Imperatori, Andrea; Nardecchia, Elisa; Rotolo, Nicola; Dominioni, Lorenzo; Scarpa, Aldo; Sessa, Fausto
Abstract: Combined neoplasms of the lung are defined by the WHO classification as an admixture of a small or large cell neuroendocrine carcinoma and a non-neuroendocrine component. However, rare cases of carcinoids combined with a non-neuroendocrine component have been described. These tumor types are not included as a specific entity in the WHO classification of pulmonary neoplasms and their pathogenesis is still unknown. We describe the clinico-pathologic and molecular features of a mixed (combined) lung neoplasm composed of adenocarcinoma and atypical carcinoid. The NGS analysis of the two different tumor components shows a similar molecular profile suggesting their monoclonal origin from a transformed stem/progenitor tumor cell which acquires a divergent differentiation during its development and progression. We also suggest the use of the recently proposed term of mixed neuroendocrine/non-neuroendocrine neoplasm (MiNEN) to define mixed (combined) neoplasms of the lung, because it seems to better cover the wide spectrum of different possible combinations of neuroendocrine and non-neuroendocrine components.